216k views
4 votes
-7/9y - 4 = 2/3y + 9

1 Answer

6 votes

For this case we must simplify the following equation:


- \frac {7} {9} y-4 = \frac {2} {3}y + 9

We subtract
\frac {2} {3}yon both sides of the equation:


- \frac {7} {9} y- \frac {2} {3} y-4 = 9

Equal signs are added and the same sign is placed:


\frac {-21-18} {27}y-4 = 9\\\frac {-39} {27}y-4 = 9\\- \frac {13} {9}y-4 = 9

We add 4 to both sides of the equation:


- \frac {13} {9} y = 9 + 4\\- \frac {13} {9} y = 13

We multiply by 9 on both sides of the equation:


-13y = 117

We divide between 13 on both sides of the equation:


-y = \frac {117} {13}\\-y = 9

We multiply by -1 on both sides of the equation:


y = -9

ANswer:


y = -9

User Nfechner
by
5.2k points